2010
DOI: 10.1016/j.bbabio.2010.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Assembly and oligomerization of human ATP synthase lacking mitochondrial subunits a and A6L

Abstract: Here we study ATP synthase from human rho0 (rho zero) cells by clear native electrophoresis (CNE or CN-PAGE) and show that ATP synthase is almost fully assembled in spite of the absence of subunits a and A6L. This identifies subunits a and A6L as two of the last subunits to complete the ATP synthase assembly. Minor amounts of dimeric and even tetrameric forms of the large assembly intermediate were preserved under the conditions of CNE, suggesting that it associated further into higher order structures in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
101
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(110 citation statements)
references
References 40 publications
8
101
0
1
Order By: Relevance
“…The function of subunit A6L is still unclear (36). Recent work by Wittig et al (82) suggests that both proteins ATPase6 and A6L are important for the stabilization of ATP synthase dimer/oligomers.…”
Section: Mitochondrial Genomementioning
confidence: 99%
“…The function of subunit A6L is still unclear (36). Recent work by Wittig et al (82) suggests that both proteins ATPase6 and A6L are important for the stabilization of ATP synthase dimer/oligomers.…”
Section: Mitochondrial Genomementioning
confidence: 99%
“…When cells are deprived of oxygen and glucose, IF1-suppressed cells lose cellular ATP and die more rapidly than control cells, suggesting a role of IF1 in maintaining ATP concentration ([ATP]) in energy crises (9). Several groups reported that IF1 facilitates dimer formation of F o F 1 in the inner mitochondrial membranes (10 -12) and contributes to cristae formation (9,(13)(14)(15)(16)(17)(18). This profound effect of IF1 on mitochondrial morphology remains controversial (19,20).…”
mentioning
confidence: 99%
“…The successful time-delayed assembly of subunit a into preformed F O F 1 -a complexes in vivo supports the view that subunit a is the last subunit being integrated into the enzyme complex (23)(24)(25), thereby finally generating a functional ATP synthase. From an energetic point of view, it appears favorable that the formation of the proton-conducting unit by interaction of subunit a with the c 10 ring is the last step during assembly, ensuring that partially assembled subcomplexes do not result in proton leakage, which might be lethal for the cell.…”
Section: Discussionmentioning
confidence: 51%
“…The minimal catalytic unit stably present in the cytoplasm is composed of ␣ 3 ␤ 3 ␥ (20, 21), and complex formation of subunit ␣ with other F 1 subunits is a prerequisite for the binding of subunit ␦ to the N-terminal region of subunit ␣ (22). In the case of both thermophilic Bacillus PS3 and human 0 cells, a stable F O F 1 subcomplex lacking subunit a can be purified (23)(24)(25), clearly indicating that the F 1 subunits are associated with the subunit c ring and the peripheral stalk prior to attachment of subunit a. The analysis of partially assembled subcomplexes is a prerequisite for defining the sequence of events in the assembly process of the ATP synthase.…”
mentioning
confidence: 99%